2010
DOI: 10.1063/1.3452364
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport properties of graphene-based ferromagnetic/singlet superconductor/ferromagnetic junctions

Abstract: We present an investigation of heat transport in gapless graphene-based Ferromagnetic /singlet Superconductor/Ferromagnetic (FG|SG|FG) junctions. We find that unlike uniform increase of thermal conductance vs temperature, the thermal conductance exhibits intensive oscillatory behavior vs width of the sandwiched s-wave superconducting region between the two ferromagnetic layers. This oscillatory form is occurred by interference of the massless Dirac fermions in graphene. Also we find that the thermal conductanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…Thermal conductance (TC) has been investigated in graphene based hybrid junctions in Ref. [38][39][40][41] where due to low-energy relativistic nature of Dirac fermions in graphene, TC exhibits oscillatory behavior with respect to the barrier strength. Such oscillatory behavior of TC is in sharp contrast to that of the conventional NS junction 42,43 where TC decays with the barrier strength.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductance (TC) has been investigated in graphene based hybrid junctions in Ref. [38][39][40][41] where due to low-energy relativistic nature of Dirac fermions in graphene, TC exhibits oscillatory behavior with respect to the barrier strength. Such oscillatory behavior of TC is in sharp contrast to that of the conventional NS junction 42,43 where TC decays with the barrier strength.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, similar expressions of the energy current in 1D topological-trivial metal superconductor junctions have been obtained by a rigorous derivation through linear response of entropy production 22 or by a heuristic argument 23 . The latter was then applied to the superconducting graphene systems 24,25 . It is worth emphasizing that all the transports considered in this work are charge neutral, i.e., the carriers transport only thermal energy without charge current.…”
mentioning
confidence: 99%
“…The thermal conductance can also be increased or decreased with respect to the temperature, depending on the strength of the exchange field in F region. We further demonstrate that in contrast to the graphene-based F/S/F structure [20], the thermal conductance displays a maximum value with respect to the exchange field at h < λ, which moves towards larger exchange fields by increasing the temperature. This paper is organized as follows.…”
Section: Arxiv:14021840v2 [Cond-matmes-hall] 7 Oct 2014mentioning
confidence: 98%
“…Furthermore, Linder et al [18] have recently demonstrated a fully spin×valley polarized pure CAR process (with sτ = −1, where s and τ indicate the spin and valley degrees of freedom) in silicene-based N/S/N structure which means that the nonlocal current is fully spin-polarized in each valley. Moreover, there has been many studies on the transport of charge, spin, and heat through the hybrid structures of normal, ferromagnetic and superconducting graphene [19][20][21].…”
Section: Introductionmentioning
confidence: 99%